ANALISIS ELEMEN-ELEMEN FRAUD HEXAGON THEORY SEBAGAI DETERMINAN FRAUDULENT FINANCIAL REPORTING - Natasya Octaviana (Jurnal Akuntansi, 2022)
The financial report is a report that presents data about the company's finances in a certain period. The importance of a financial report will be a trigger for company management to take various ways so that the company's financial statements always look good. This study uses agency theory, which is a theory that explains the relationship between shareholders (principals) and management (agents), where the agent is tasked with carrying out every order from the principal to improve company performance so that it can put pressure on agents to commit financial statement fraud. The sample of this research is infrastructure, utility, and transportation companies listed on the IDX during the 2018-2020 period, totaling 45 companies so as to obtain 135 research samples. This research was conducted with non-probability sampling technique and purposive sampling method. The tests in this research are pooling test and logistic regression analysis test. This study states that the variables of financial stability, nature of industry, and the ratio of total accruals have a positive and significant effect on the possibility of fraudulent financial reporting. The financial target variable has a negative and significant effect on the possibility of fraudulent financial reporting. Meanwhile, external pressure, ineffective monitoring, change in auditor, CEO's education, frequent number of CEO's pictures, and state-owned enterprises variables have no significant effect on the possibility of fraudulent financial reporting. Suggestions for further researchers are to add other independent variables such as personal financial needs, CEO duality, change in directors, and political connection as variables that can trigger financial statement fraud.